TRANSFORMATION OF TEXT NATURAL LANGUAGE INFORMATION ON THE BASIS OF VERBAL SEMANTIC UNITS - Сич, М. (Science-based technologies, 2012)
In the article described mechanism of text information on natural language transformation for purposes of processing by computer systems word constructions with different particular words senses but the same common sense. Transformation is based on the set of semantic nodes patterns, which can be lain on actual natural language text information.